THE INFLUENCE OF ASSET STRUCTURE, PROFITABILITY, AND COMPANY SIZE ON CAPITAL STRUCTURE IN. BANK NEGARA INDONESIA TBK - Tiara Lilis Surya (LP2M Universitas Bina Bangsa, 2024)
This study aims to determine: 1. Effect of asset structure (FAR) on capital structure. 2.Effect of profitability (ROA) on capital structure. 3. Effect of company size (Ln Total Assets) on capital structure. 4. The influence of asset structure, profitability, and company size on capital structure. 5. Big surprise effect of activation structure, profitability, and firm size on capital structure. Based on the research results show that: 1) there is a significant influence between the activation structure on the capital structure at PT. Bank Negara Indonesia Tbk Period 2012-2021. 2) there is no significant effect between profitability on capital structure at PT. Bank Negara Indonesia Tbk Period 2012-2021. 3) there is no significant effect between company size on the capital structure at PT. Bank Negara Indonesia Tbk Period 2012-2021. 4) there is a significant influence between the structure of assets, profitability, and company size on the capital structure at PT. Bank Negara Indonesia Tbk Period 2012-2021.5) The magnitude of the effect of Asset Structure, Profitability, and Company Size on Capital Structure is 70.8% while the remaining 29.2%.